Penentuan Konsentrasi Dan Volume Demulsifier Pada Proses Pengolahan Minyak Di CGS - 1 Pt. Chevron Pacific Indonesia Duri,Riau - Pasaribu, Ade Susanto; Fadli, Ahmad; Akbar, Fajril (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Central Gathering Station (CGS - 1), a facility to process fluid that is pumped from the production wells in duri city. Fluid flowing into the CGS - 1 will be separated into water, oil and solids, then the fluid is heated using a heat exchanger so that the separation between oil and water is better, but the heat is not enough for separation because of the persistence of the emulsion. For that use a chemical called demulsifier that serves to solve the water in oil emulsion so that the quality of oil in accordance with its terms. Emulsion enormous influence in lowering the quality of the oil  .Proper demulsifier concentration and sampling were both very helpful to reach the expected quality of the oil . The study was conducted to determine the concentration and volume of demulsifier on oil processing in CGS-1 with demulsifier reinjection method with variations of volume 1,0 ml to 5,5 ml and the variation of concentration of 50% to 100%, with samples taken from the incoming fluid CGS-1 with Basic Sediment and water cut 92% . After the sample was separated obtained 20% of water cut, then conducted research with injecting demulsifier with some variation of the above and the most optimal results obtained by the injection of 5,0 ml with a concentration of 70% water cut can lose up to 0.9%  Keywords: emulsion, injection, demulsifier, water cut